Local government authority attitudes to road traffic CO2 emissions modelling: a British case study. Issue 1 (2nd January 2017) - Grote, Matt; Williams, Ian; Preston, John; Kemp, Simon
ABSTRACT: Local government authorities (LGAs) play a key role in facilitating mitigation of road traffic CO2 emissions and must engage in emissions modelling to quantify the impact of transport interventions. Existing Emissions Model (EM) methodologies range from aggregate to disaggregate approaches, with more detail normally entailing more resources. However, it is not clear which approaches LGAs actually utilise. This article reports results of a survey designed to discover the level of detail considered practical by British LGAs ( n  = 34). Results show that resource scarcity is important, with particular importance attached to EM reusability and convenient input data sources. Most LGA EMs use traffic variable inputs (predominantly traffic flow and traffic average speed), with this approach being the best-fit for LGA resources. Link-by-link sources of data rated highly for convenience are Road Traffic Models and Urban traffic control systems.